Calibration campaign against the international prototype of the kilogram in anticipation of the redefinition of the kilogram part I: comparison of the international prototype with its official copies. (24th March 2015) - Stock, Michael; Barat, Pauline; Davis, Richard S; Picard, Alain; Milton, Martin J T
Abstract: This report presents the results of the first phase of the campaign of calibration carried out with respect to the international prototype of the kilogram (IPK) in anticipation of the redefinition of the kilogram ( Extraordinary Calibrations ). The definition of the kilogram was realized according to the procedure outlined in the 8th Edition of the SI Brochure. Thus the IPK and its six official copies have been cleaned and washed following the BIPM procedure. The mass comparisons carried out during this campaign showed a very good repeatability. The pooled standard deviation of repeated weighings of the prototypes was 0.4 µg. The effect of cleaning and washing of the IPK was to remove a mass of 16.8 µg. The effect of cleaning and washing of the six official copies was found to be very similar, giving an average mass removed from the seven prototypes of 15 µg with a standard deviation of 2 µg. The differences in mass between the IPK and the official copies have changed by an average of 1 µg since the 3rd Periodic Verification of National Prototypes of the Kilogram (1988–1992). These results do not confirm the trend for the masses of the six official copies to diverge from the mass of the IPK that was observed during the 2nd and 3rd Periodic Verifications. All BIPM working standards and the prototypes reserved for special use have been calibrated with respect to the IPK as part of this campaign. All of them were found to have lower masses than when they were calibrated during the 3rd Periodic Verification. As a consequence, the BIPM 'as-maintained' mass unit in 2014 has been found to be offset by 35 µg with respect to the IPK. This result will be analyzed in a further publication.